Effects of pre-surgery physiotherapy on walking ability and lower extremity strength in patients with degenerative lumbar spine disorder: Secondary outcomes of the PREPARE randomised controlled trial - Fors, Maria (BMC Musculoskelet Disord, 2019)
BACKGROUND: Degenerative lumbar spine disorders are common among musculoskeletal disorders. When disabling pain and radiculopathy persists after adequate course of rehabilitation and imaging confirms compressive pathology, surgical decompression is indicated. Prehabilitation aiming to augment functional capacity pre-surgery may improve physical function and activity levels pre and post-surgery. This study aims to evaluate the effect and dose-response of pre-surgery physiotherapy on quadriceps femoris strength and walking ability in patients with degenerative lumbar spine disorders compared to waiting-list controls and their association with postoperative physical activity level. METHOD: In this single blinded, 2-arm randomised controlled trial, 197 patients were consecutively recruited. Inclusion criteria were: MRI confirmed diagnosis and scheduled for surgery due to disc herniation, lumbar spinal stenosis, degenerative disc disease or spondylolisthesis, ages 25-80 years. Patients were randomised to 9 weeks of pre-surgery physiotherapy or to waiting-list. Patient reported physical activity level, walking ability according to Oswestry Disability Index item 4, walking distance according to the SWESPINE national register and physical outcome measures including the timed ten-meter walk test, maximum voluntary isometric quadriceps femoris muscle strength, patient-rated were collected at baseline and follow-up. Parametric or non-parametric within and between group comparisons as well as multivariate regression was performed. RESULTS: Patients who received pre-surgery physiotherapy significantly improved in all variables from baseline to follow-up (p < 0.001 – p < 0.05) and in comparison to waiting-list controls (p < 0.001 – p < 0.028). Patients adhering to ≥12 treatment sessions significantly improved in all variables (p < 0.001 – p < 0.032) and those receiving 0-11 treatment session in only normal walking speed (p0.035) but there were no significant differences when comparing dosages. Physical outcome measures after pre-surgery physiotherapy together significantly explain 27.5% of the variation in physical activity level 1 year after surgery with pre-surgery physical activity level having a significant multivariate association. CONCLUSION: Pre-surgery physiotherapy increased walking ability and lower extremity strength in patients with degenerative lumbar spine disorders compared to waiting-list controls. A clear treatment dose-response response relationship was not found. These results implicate that pre-surgery physiotherapy can influence functional capacity before surgical treatment and has moderate associations with maintained postoperative physical activity levels mostly explained by physical activity level pre-surgery. TRIAL REGISTRATION: NCT02454400. Trial registration date: August 31st 2015, retrospectively registered.